2018
DOI: 10.1016/j.bbadis.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 functions as a switch for phenotype transformation and proliferation of VSMCs in hypertensive vascular remodeling

Abstract: The phenotypic transformation from differentiated to dedifferentiated vascular smooth muscle cells (VSMCs) plays a crucial role in VSMC proliferation and vascular remodeling in many cardiovascular diseases including hypertension. Nesfatin-1, a multifunctional adipocytokine, is critically involved in the regulation of blood pressure. However, it is still largely unexplored whether nesfatin-1 is a potential candidate in VSMC phenotypic switch and proliferation in hypertension. Experiments were carried out in Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…Peripheral nesfatin-1 exerts pronounced effects on the cardiovascular system, namely an increase in blood pressure after IP administration in mice [ 139 ] and rats [ 140 ] or IV injection in rats [ 141 ], with inhibited relaxation of peripheral blood vessels probably contributing to this effect [ 141 ]. This effect is likely associated with stimulated signaling of the phosphoinositide-3-kinase (PI3K)/AKT/ m -TOR pathway and phosphorylation of Janus kinase 2 (JAK2)/STAT3, resulting in proliferation, migration, and phenotype switch of vascular smooth muscle cells from a contractile to a synthetic state by elevating the mRNA and protein expression of matrix metalloproteinase 2 and 9 while reducing peroxisome proliferator-activated receptor-γ [ 142 , 143 ]. Because NUCB2 mRNA expression was increased in the media of the aorta of spontaneously hypertensive rats [ 142 ], nesfatin-1 might play a pathogenetic role under these conditions.…”
Section: Implications Of Nesfatin-1 In Cardiovascular Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral nesfatin-1 exerts pronounced effects on the cardiovascular system, namely an increase in blood pressure after IP administration in mice [ 139 ] and rats [ 140 ] or IV injection in rats [ 141 ], with inhibited relaxation of peripheral blood vessels probably contributing to this effect [ 141 ]. This effect is likely associated with stimulated signaling of the phosphoinositide-3-kinase (PI3K)/AKT/ m -TOR pathway and phosphorylation of Janus kinase 2 (JAK2)/STAT3, resulting in proliferation, migration, and phenotype switch of vascular smooth muscle cells from a contractile to a synthetic state by elevating the mRNA and protein expression of matrix metalloproteinase 2 and 9 while reducing peroxisome proliferator-activated receptor-γ [ 142 , 143 ]. Because NUCB2 mRNA expression was increased in the media of the aorta of spontaneously hypertensive rats [ 142 ], nesfatin-1 might play a pathogenetic role under these conditions.…”
Section: Implications Of Nesfatin-1 In Cardiovascular Functionsmentioning
confidence: 99%
“…This effect is likely associated with stimulated signaling of the phosphoinositide-3-kinase (PI3K)/AKT/ m -TOR pathway and phosphorylation of Janus kinase 2 (JAK2)/STAT3, resulting in proliferation, migration, and phenotype switch of vascular smooth muscle cells from a contractile to a synthetic state by elevating the mRNA and protein expression of matrix metalloproteinase 2 and 9 while reducing peroxisome proliferator-activated receptor-γ [ 142 , 143 ]. Because NUCB2 mRNA expression was increased in the media of the aorta of spontaneously hypertensive rats [ 142 ], nesfatin-1 might play a pathogenetic role under these conditions. In line with this assumption, circulating NUCB2/nesfatin-1 levels were higher in patients with essential hypertension than in normotensive controls and correlated with systolic blood pressure [ 144 ]; therefore, nesfatin-1 has been suggested as a risk factor for obesity-associated hypertension (OR 1.5) [ 145 ].…”
Section: Implications Of Nesfatin-1 In Cardiovascular Functionsmentioning
confidence: 99%
“…MAPK signaling is closely related to cell growth and proliferation [35]. Lu et al showed that nesfatin-1 promoted the proliferation and migration of VSMCs by enhancing the activity of PI3K/ AKT/mTOR [36]. Vaspin inhibited high glucose-induced proliferation and migration of VSMCs induced by inhibiting MAPK and PI3K/AKT signaling [37].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of mTOR inhibition and de ciency on vascular remodeling differs in physiological and pathological status [47]. The PI3K signaling pathway and its major downstream effector protein kinase B (PKB/Akt) are involved in glucose metabolism, differentiation, proliferation, apoptosis, cell migration and in ammatory responses [48,49]. Many diseases, including diabetes, atherosclerosis, hypertension, and cancers, are associated with abnormal loss or activation of the PI3K/Akt pathway [50].…”
Section: Discussionmentioning
confidence: 99%